Panchromatic light harvesting and record power conversion efficiency for carboxylic/cyanoacrylic Fe(ii) NHC co-sensitized FeSSCs. Issue 16 (3rd April 2023) - Reddy-Marri, Anil; Marchini, Edoardo; Cabanes, Valentin Diez; Argazzi, Roberto; Pastore, Mariachiara; Caramori, Stefano; Gros, Philippe C.
Abstract : The co-sensitization of TiO2 by using a combination of carboxylic and thienylcyanoacrylic (ThCA)–Fe(ii ) pyridyl-NHC sensitizers produced a panchromatic absorption and the best photocurrent and efficiency ever reported for an FeSSC. Abstract : Fe(ii ) pyridyl-NHC sensitizers bearing thienylcyanoacrylic (ThCA) anchoring groups have been designed and characterized with the aim of enhancing the metal to surface charge separation and the light harvesting window in iron-sensitized DSSCs (FeSSCs). In these new Fe(ii ) dyes, the introduction of the ThCA moiety remarkably extended the spectral response and the photocurrent, in comparison with their carboxylic analogues. The co-sensitization based on a mixture of a carboxylic and a ThCA–iron complex produced a panchromatic absorption, up to 800 nm and the best photocurrent and efficiency ( J sc : 9 mA cm −2 and PCE: 2%) ever reported for an FeSSC.